Systematic Literature Review of Digitalization and Economic Empowerment as Pillars of a Smart Coastal Economy - Irawati HM; Etty Wahyuni; Rusdy Setiawan; Muh. Irfandy Azis; Nurzhahratul Lailiah; Dwi Prayoga; Nabilah Febriyanti (Universitas Pendidikan Ganesha, 2026)
The concept of Smart Coastal Economy (SCE) has emerged as a strategic approach to achieving sustainable coastal development through digital transformation and community empowerment. However, existing research largely examines digitalization and economic empowerment as separate domains, resulting in limited conceptual integration and the absence of a systematic synthesis explaining how both interact to shape coastal economic transformation. This gap hinders the development of an integrated analytical foundation for implementing SCE strategies, particularly in emerging coastal regions. This study aims to synthesize recent empirical evidence on digitalization and economic empowerment in coastal development to construct an integrative conceptual framework for SCE. A SLR was conducted using the PRISMA framework. Articles were retrieved from indexed academic databases, including Google Scholar, MDPI, IOP Science, ScienceDirect, PubMed, IEEE Xplore, and Elsevier. Publications were limited to the period from March 1, 2020, to February 28, 2025. The findings reveal three principal results. First, digitalization enhances coastal competitiveness and sustainability through improved resource efficiency, expanded market access, strengthened supply chain transparency, and environmentally responsible resource management; however, its effectiveness is conditional upon infrastructure readiness, governance support, and community digital literacy. Second, economic empowerment strengthens community capacity across economic, social, and institutional dimensions, particularly when integrating digital skills development, institutional strengthening, digital entrepreneurship, and ecological awareness. Third, the integration of digitalization and empowerment forms a structurally interdependent framework that generates systemic outcomes efficiency and productivity, socio-economic inclusion, and sustainability and resilience. These results provide an evidence-based conceptual foundation for advancing SCE strategies.